Simulasi Metode Monte Carlo Untuk Memprediksi Jumlah Kunjungan Pasien Puskesmas Batang Kuis - Sindy Fitriani Margaret Sihaloho (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Community Health Centers (Puskesmas) are the main place for the public to get basic health services. In certain conditions, the Health Center will receive visits from patients who arrive with the same number of origins at the same time. This has an impact on health services experiencing a decline and not maximizing the health of health workers in checking patients' health. So, comprehensive services are not obtained, and there are even patients who queue for too long. In order to minimize this occurrence, simulations are carried out to predict the number of possible visits that will occur in the future. The method used in this study is Monte Carlo. This research is intended so that the information provided by the Health Center related to the prediction of the number of patient visits that are likely to occur in the next year or in the future can be done validly and accurately. The data used is data on the number of patient visits in 2021, 2022, and 2023. As a result of this study, a prediction of the number of patient visits was obtained so that the Health Center could implement the next action that was useful for improving the quality of services needed